Toll-like receptors and macrophage activation in atherosclerosis. - Seneviratne, A; Sivagurunathan, B; Monaco, C (2012)
Atherosclerosis is a multi-factorial inflammatory disease and is the primary initiator of coronary artery and cerebrovascular disease. Initially believed to be exclusively lipid-driven, recent evidence demonstrates that inflammation is a significant driving force of the disease. Cellular components of innate immunity, for example monocytes and macrophages, play a predominant role in atherosclerosis. Toll-like receptors (TLRs) are the most characterised innate immune receptors and recent evidence demonstrates an important role in atherogenesis. Engagement of TLRs results in the transcription of pro-inflammatory cytokines, foam cell formation and activation of adaptive immunity. Recently they have also been implicated in protection from vascular disease. In this review, we detail the role of the innate immune system, specifically macrophages and TLR signalling, in atherosclerosis and acute cardiovascular complications, and thereby identify the potential of TLRs to act as therapeutic targets.